Ownership Structure, Deregulation, and Bank Risk Taking. - Saunders, Anthony; Strock, Elizabeth; Travlos, Nickolaos G (Journal of Finance, 1990)
This paper investigates the relationship between bank ownership structure and risk taking. It is hypothesized that stockholder controlled banks have incentives to take higher risk than managerially controlled banks and that these differences in risk become more pronounced in periods of deregulation. In support of this hypothesis, the authors show that stockholder controlled banks exhibit significantly higher risk taking behavior than managerially controlled banks during the 1979-82 period of relative deregulation.